Uma proposta de aferição de índices baseado em DEA e uma aplicação ao caso das Universidades Federais Brasileiras - Lima, Luciana Belo de (2017)
The objective of this research was to present an alternative form of efficiency indexes based on the realities presented by the agents under study. In this study, the agents studied were the Institutions of Higher Education (HEI) in the country. The methodology used was Data Envelopment Analysis (DEA), model Charnes, Cooper and Rhodes (CCR), with limits on the variables, which has as inputs the resources received by the institutions and as outputs all the products offered by these institutions. Given the measure obtained by this methodology, we investigated the adherence of this model to the current model applied by governmental institutions in the evaluation of these institutions. As a result, it was possible to observe that the federal universities are not considered compatible from the point of view of efficiency, because, according to the scenarios created, only 2 universities have achieved their efficiency, while the General Index of Courses (IGC), 11 universities were considered efficient. Thus, it was verified that the efficiency analysis model is considered to be applicable and significant, serving for the managers of the federal educational institutions to reassess whether the IGC quality indicator is considered efficient to evaluate the HEIs comprehensively, in order to maximize results while keeping resources constant over the long term.